Individual differences in Sabahan highland farmers' adaptation towards climate change - Idris, Khairuddin; Fadzil, Mohd Fauzi; Abu Samah, Bahaman; Abu Samah, Asnarulkhadi; Mohamed Shaffril, Hayrol Azril (Human Resource Management Academic Research Society, 2018)
This paper discusses the individual differences in adaptation towards climate change among Sabahan highland farmers. This study is quantitative in nature in the form of a cross-sectional survey. Via a simple random sampling, a total of 200 highland farmers in Kundasang and Moyog were selected as respondents. The analysis performed has concluded that the differences in education achievement have a significant influence on Sabahan highland farmers’ adaptation towards climate change, while factors such as age, income and the number of household members have a significant relationship with their adaptation towards climate change. A number of recommendations were highlighted and it is a hope that it can assist related parties in constructing a better community’s adaptation plan.